MODERN METHODS OF DIAGNOSIS OF ENTEROVIRUS INFECTION IN THE MOUTH - Bublii, T.D.; Dubovaya, L.I. (World of Medicine and Biology, 2018)
The actual problem of modern clinical medicine there are viral lesions. The incidence of infectious diseases caused by enteroviruses (EVIE) significant increase in the last years. It is known that the incidence of EVIE continues to grow. Approximately 75% of EVIE, who registered annually are in children under 15 years of age. Clinical manifestations in most patients characterized by lesions of the central nervous system, development of respiratory distress syndrome and, consequently, a high percentage of mortality. Every 3-4 year recorded epidemic outbreaks of diseases that are caused by the different serotypes of the virus. The aim of our study is to draw attention to the increasing frequency of dental manifestations of EVIE in the oral cavity, modern methods of diagnostics, treatment and prevention of enterovirus infection. Materials and methods: the analysis of the problem of EVIE in dentistry is based on published data, as well as their own clinical observations. The enterovirus includes Poliovirus, Echovirus, Coxsakievirus, and numbered types of Non polio enteroviruses. They are the smallest in size of RNA viruses. Enteroviruses cause a wide range of symptoms, and while their long list of signs and symptoms should put them on the differential diagnosis list of many illnesses, they often go unnoticed. Enteroviruses can cause anything from rashes in small children, to summer colds, to encephalitis, to blurred vision, to pericarditis. Enteroviral infections have a great range in presentation and seriousness. Ironically, although the virus is named in for the transmission route into the body, one of the few illnesses not associated with enteroviruses are gastrointestinal in nature. Non polio enteroviruses cause 10-15 million infections and tens of thousands of hospitalizations in the US each year. Leading the enteroviral infection transmission are fecal-oral and air-drop. After infection with enteroviruses primarily produced virus-neutralizing antibodies, IgM class first and then IgG, that continue to be generated throughout life, albeit with a gradual decrease in titer. The article deals the manifestations of enterovirus infection in the mouth. Herpangina, also called mouth blisters, is a painful mouth infection caused by Coxsackie viruses. Symptoms include sudden fever with sore throat, headache, loss of appetite, and often neck pain. Within two days of onset an average of four or five (but sometimes up to twenty) 1 to 2 mm diameter grayish lumps form and develop into vesicles with red surrounds, and over 24 hours these become shallow ulcers, rarely larger than 5 mm diameter, that heal in one to seven days. These lesions most often appear on the tonsillar pillars (adjacent to the tonsils), but also on the soft palate, tonsils, uvula, or tongue. Enteroviruses can be identified through cell culture or PCR assay, collected from fecal or respiratory specimens. Enterovirus test is a single use rapid membrane immunoassay for the qualitative detection of Enterovirus antigen (VP1 peptide) in faeces samples to aid in the diagnosis of Enterovirus infection.